2014
DOI: 10.1128/jvi.02649-13
|View full text |Cite
|
Sign up to set email alerts
|

Beta Interferon Regulation of Glucose Metabolism Is PI3K/Akt Dependent and Important for Antiviral Activity against Coxsackievirus B3

Abstract: An effective type I interferon (IFN)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 99 publications
5
65
0
Order By: Relevance
“…As IFN-β has been shown to directly regulate glucose metabolism (26), it seemed possible that viral-induced glycolysis in pDCs could be mediated by IFN-α/β. To test this, we exposed pDCs to IFN-α and measured 13 C-lactate production.…”
Section: Resultsmentioning
confidence: 99%
“…As IFN-β has been shown to directly regulate glucose metabolism (26), it seemed possible that viral-induced glycolysis in pDCs could be mediated by IFN-α/β. To test this, we exposed pDCs to IFN-α and measured 13 C-lactate production.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose and mechanism underlying this observation remains to be elucidated. The precise mechanism whereby IFN signaling converges with glucose utilization programs also remains to be fully resolved, but recent studies demonstrated that interferon signaling leads to changes in glucose uptake, which is important for the antiviral response (Burke et al, 2014). Thus, whereas alternative fuel substrate availability is coupled to and necessary for adaptation to bacterial inflammation, glucose availability is coupled to and necessary for cellular adaptation to viral inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, IFNβ stimulates a PI3K/AKT-dependent glucose uptake in mouse embryonic fibroblasts that may enhance ATP production (32). Inhibition of IFNβ-induced glycolysis with 2-deoxyglucose (2-DG), a competitive inhibitor of hexokinase, the first enzyme in the glycolysis cascade, enhances replication of coxsackievirus B3 in vitro (32). This suggests that enhanced glycolysis may support the establishment of an antiviral state.…”
Section: Effects Of Ifns On Energy Metabolismmentioning
confidence: 99%